Transient Analysis of 9-Bus System using ETAP - Jha, Rahul Kumar (Technical Journal, 2023)
This research paper presents a transient analysis of a 9-bus power system using ETAP software. The simulation results obtained from ETAP are analyzed in terms of voltage and current waveforms, fault current magnitudes. However, the system experiences voltage and current fluctuations during fault conditions, which can lead to instability if not properly addressed.